Education linguistic model in teaching English as a second language: a discourse analysis - Ojanola, Raleigh (Technium Social Sciences Journal, 2022)
This paper aimed to describe the use of Education Linguistic Model in teaching English as a Second Language using discourse analysis. The study focused to the four (4) ESL teachers’ process in teaching English as a second language to the different groups of ESL learners in Koronadal National Comprehensive High School for the school year 2017-2018. The participants were selected based from the inclusion criteria formulated by the researcher: a) A participant must be a graduate of Bachelor in Secondary Education major in English; b) A participant must have an at least fifteen (15) years of experience in teaching English as a second language; and c) A participant must be one of the top ten (10) performing teachers as based from the Individual Performance Commitment and Review Form (IPCRF). Furthermore, classroom observation method was used to record classroom proceedings through field notes and voice recorder. Also, qualitative discourse analysis was employed to interpret and understand on how the four (4) ESL teachers utilize the seven (7) ELM categories which are building rapport, acknowledging success, modelling, addressing challenging behaviors, scaffolding the learning, responding to the individual learner and self-monitoring the teaching. The findings entail that the manifestations of ELM categories are evident in the process of teaching as a second language as reflected by the four (4) ESL teachers, but the process of exhibiting the ELM categories is unique and different compared among the ESL teachers. However, some of the categories are not consistently used in every class proceeding. Thus, modelling is not manifested by Teacher C and scaffolding the learning is not manifested by Teacher D. Moreover, both Teacher C and Teacher D do not manifest self-monitoring the teaching. Therefore, the study suggests that self-monitoring the teaching should be observed by the ESL teachers to enhance the process of teaching English as a second language in an ESL classroom.